2006
DOI: 10.1002/dir.20055
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure or utility? Time planning style and Web usage behaviors

Abstract: The present research focuses on time planning style, an individual's habitual approach to time management, in relation to the use of the Web. We theorize and provide empirical evidence that highly analytic versus spontaneous planners are more likely to seek utilitarian rather than hedonic benefits from Web use. This pattern is associated with downstream relationships between the types of benefits sought and various Web usage behaviors (e.g., exploratory, entertainment, information search, and electronic shoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 37 publications
1
69
0
3
Order By: Relevance
“…In particular, Cotte et al [73] argue that in the case of networked IT, hedonic motivation is closely linked to interactions with others. Given that gamified smart tourism applications are inherently network-based ICT, we here seek to distinguish utilitarian motives and hedonic motives.…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%
“…In particular, Cotte et al [73] argue that in the case of networked IT, hedonic motivation is closely linked to interactions with others. Given that gamified smart tourism applications are inherently network-based ICT, we here seek to distinguish utilitarian motives and hedonic motives.…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%
“…For example, evidence suggests that as online behaviour is often driven by a search for new experiences, challenges and sensory stimulation (Cotte et al, 2006), this can lead to a state of deep involvement (Pöyry, et al, 2013;Csikszentmihalyi, 1991) in which consumers have been found to explore new sites and click on unfamiliar links to find yet further new and interesting experiences and challenges (Cotte et al, 2006). Thus, we hypothesize that:…”
Section: Attention To Advertisements On Snssmentioning
confidence: 99%
“…As avenues to extend escape, research suggests that SNS users are more likely to click and explore unfamiliar material (Cotte et al, 2006). Therefore, we hypothesize as follows:…”
Section: Attention To Advertisements On Snssmentioning
confidence: 99%
“…Their likelihood of visiting a corporate website is hypothesized to be higher, if the company is well known. task-focused, hedonic Web use is characterized by people's search for sensory stimulation (Cotte et al, 2006). These two concepts originate from the marketing field, where hedonic consumption denotes "those facets of consumer behavior that relate to the multisensory, fantasy and emotive aspects of one's experience with products" (Hirschmann & Holbrook, 1982, p. 92).…”
Section: Trustworthiness and Source Reputationmentioning
confidence: 99%
“…Childers et al, 2001;Cotte et al, 2006;Hartmann et al, 2006;Overby & Lee, 2006). Accordingly, it is hypothesized that there is a positive relationship between people's hedonic and utilitarian use of corporate websites and their likelihood of retrieving content from corporate websites.…”
Section: Trustworthiness and Source Reputationmentioning
confidence: 99%